2018
DOI: 10.1167/tvst.7.6.22
|View full text |Cite
|
Sign up to set email alerts
|

Combined Targeted Analysis of Metabolites and Proteins in Tear Fluid With Regard to Clinical Applications

Abstract: PurposeTo establish a robust workflow for combined mass spectrometry–based analysis of metabolites and proteins in tear fluid with regard to clinical applicability.MethodsTear fluid was taken from 12 healthy volunteers at different time points using specially designed Schirmer strips. Following the liquid extraction of metabolites from standardized punches, the remaining material was processed for bottom-up proteomics. Targeted metabolite profiling was performed adapting a metabolomics kit, which targets 188 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…The efficiency of the selected PVP-loaded DNT-OL-500 lens in stabilizing the tear film was investigated using Schirmer tear test (New Zealand rabbit model). [56][57][58] The study include 4 groups (n ¼ 6): The test was started before 3 days of contact lens insertion and continued for next 7 days (total 10 days study). The Schirmer strip (Tianjin Jingming New Technological Development Co., Ltd. Tianjin, China) of 5 Â 35 mm was placed inside the margin of the inferolateral (third) of the lower eyelid for 2 min (every 24 h) and the strip wetting was measured in mm and plotted versus time (days).…”
Section: Schirmer Strip Testmentioning
confidence: 99%
“…The efficiency of the selected PVP-loaded DNT-OL-500 lens in stabilizing the tear film was investigated using Schirmer tear test (New Zealand rabbit model). [56][57][58] The study include 4 groups (n ¼ 6): The test was started before 3 days of contact lens insertion and continued for next 7 days (total 10 days study). The Schirmer strip (Tianjin Jingming New Technological Development Co., Ltd. Tianjin, China) of 5 Â 35 mm was placed inside the margin of the inferolateral (third) of the lower eyelid for 2 min (every 24 h) and the strip wetting was measured in mm and plotted versus time (days).…”
Section: Schirmer Strip Testmentioning
confidence: 99%
“…In these experiments we identified a high variability in the levels of MUC5AC among different individuals, with coefficients of variation greater than 50%. Previous studies have shown that the inter-individual variability appears to be dependent of the specific component being analyzed in the tear film and its secretion rate [ 12 , 18 ]. In this regard, MUC5AC is produced by goblet cells in the conjunctiva but the mechanisms regulating its secretion remain largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…6 Another study has used a specially designed Schirmer strip with standardized punches of 4 mm in diameter that were cut out for protein and metabolite analysis, discarding the remaining wetted part of the Schirmer strip. 7 Although these approaches standardize collection volume, discarded tear-absorbed portions may include significant concentrations of some chemical components, and these discarded portions should be always assessed to evaluate the validity of the research protocol.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The most commonly used methods for noninvasive tear analysis in both clinical and research settings from humans and animal models involve collection and processing via absorbent material, such as thread and filter paper. [6][7][8][9][10][11][12][13][14][15][16][17] Yet the impact of these analytical methods on the chemical composition of tear fluid is largely unexplored. It is crucial to define the impacts of collection and processing methods on tear analysis to standardize results drawn from different studies.…”
Section: Introductionmentioning
confidence: 99%